Hypoglycemic, hepatoprotective, and hypolipidemic effects of hydroalcoholic extract of Eryngium billardieri root on nicotinamide/streptozotocin-induced type II diabetic rats - Samira Khani; Maasoume Abdollahi; Zeynab Asadi; Mohamad Nazeri; Mohammad Amin Nasiri; Hossein Yusefi; Abbas Moghadam; Hamid Heidari (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Erynginum billardieri has been used to control diabetes in traditional medicine. This research was performed to study the antidiabetic, hepatoprotective, and hypolipidemic effects of E. billardieri root extract (EBRE) on streptozotocin/nicotinamide-induced type 2 diabetic male rats. Experimental approach: Type two diabetic animals were treated by three different doses of EBRE (100, 200, and 400 mg/kg), orally administered for 4 weeks. Ultimately, after anesthesia, the glucose, insulin, lipid profiles, hepatic enzyme levels in the blood and liver, and pancreas tissues of the animals were analyzed. Findings/Results: Induction of diabetes caused a diminution in insulin level, high-density lipoprotein (HDL), and significantly enhanced the level of other lipid profiles, glucose, and liver enzymes (P < 0.05). Administration of the EBRE to diabetic-male rats significantly reduced glucose level, lipid profiles, and liver enzymes, and increased the level of HDL to near normal. Conclusion and implications: The results of the present study showed that E. billardieri had a positive effect on diminishing the lipid profiles, liver enzymes, and controlling diabetes. The most effective dose was found to be 100 mg/kg.